MODELING OF AN AIRPLANE WING MOMENTS INDUCED BY ATMOSPHERIC TURBULENCE - Antonova, Anna; Kulyk, Mykola; Lastivka, Ivan (Proceedings of National Aviation University (archive), 2014)
We have used Diederich’s theory of wingspan average correlation functions to obtain analytical expressions for the local spectral density of aircraft wing moments induced by horizontal and vertical wind gusts. We have assumed that the correlation functions of atmospheric turbulence belong to the Bullen family which includes both partial cases of known Dryden’s model as well as von Karman’s model.